Swami and his friends at the Malgudi post office - Raghuram, G., active 1996 (London : Indian Institute of Management, Ahmedabad, 1996)
The case aims to teach students about the problems and pitfalls of modernisation and improving efficiency. The case sets out the problem of a fictional post office, with average wait times for different services. The student is then invited to work out whether the introduction of a new computer system will reduce waiting times.
Originally published in Raghuram. G. (1996). Swami and his Friends at the Malgudi Post Office. QM0238. Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Production management